Effect of paclobutrazol on lodging resistance, growth and yield of direct seeded rice - Syahputra, Bambang Surya Adji (2012)
The study was initiated to observe the effects of paclobutrazol (PBZ) as foliar spray on growth, lodging resistance and yield of direct seeded rice. The study consisted of two field experiments and one glasshouse experiment. The field trials were conducted in MADA, Kedah and IADA, Seberang Perak, Perak over two rice growing seasons. The first field trial was designed to obtain the optimum paclobutrazol concentration for increased lodging resistance in one variety of field grown rice, namely MR 219. Paclobutrazol at varying concentrations (0, 100, 200, 400 and 600 mg/L) was applied to rice plants at panicle initiation stage (56 DAS). In the second trial, the best concentration obtained in experiment 1 was used to obtain best time of application. Plants were sprayed at one week before (B) Panicle initiation (PI), during (D) PI and one week after (A) PI. The third experiment was conducted at glass house Ladang 2 UPM to understand the relationship between bending resistance and the ability to withstand wind speeds using a wind tunnel. The results of the first experiment with variety MR219 showed a significant reduction in plant height both at two weeks after application (2WAA) and at harvest with 400 and 600 mg/L having shorter plants compared to control. The culm and internode length was shorter due to retardation of the lower internodes in plants treated with 400 mg/L. Culm histology revealed that, following the increase in PBZ concentration, parenchyma cell shape changed from rounded to hexagonal with reduced intercellular space. The above changes increased bending resistance significantly with 400 and 600 mg/L of PBZ. Flag leaf area was reduced but chlorophyll content was higher for treatments with 400 and 600 mg/L. Yield and yield components showed that fresh and dry weight was significantly increased at 400 and 600 mg/L compared to control. Panicle length, panicle/m2 and weight of 1000 grains were not significantly different for all treatment compared to control plant. It was concluded that the optimum concentration of PBZ was 400 mg/L as minimal differences were observed between 400 and 600 mg/L. In the second experiment with variety MR 219 in Kedah, plant height , culm length and flag leaf area was significantly reduced for treatment B and D. Bending resistance and chlorophyll concentration was increased for all treatment (B, D and A) at p<0.05 respectively. Internodes length was not significantly different in treatment A compared to control plant for uppermost and second internode, but was significantly different in treatment B and D compared to control plant. Yield and yield components increased for all treatment (B, D and A) compared to control plant. Similar response was obtained in two locations over two seasons. PBZ application it better done at one week before PI. The third experiment was conducted to understand the relationship between the plant architecture and resistance to wind using a wind tunnel. Upon exposure to wind at 120 km/hour for 5 minutes, the plants were kept in glasshouse for 24 hours, variety MR 219 treated with 400 mg/L Paclobutrazol was 10 to 16% lodged while plants treated with 100 mg/L, 200 mg/L and untreated plants had 60-70%, 40-50% and 90% lodging respectively.PBZ at a concentration of 400 mg/L applied one week before PI was found to be optimum for reduction in plant height and culm height, increase bending resistance and yield with similar effect in both location and for both seasons suggesting its effect to be stable across different environmental conditions.